SOWING QUALITIES OF MEDICINAL PLANTS’ SEEDS DEPENDING ON THEIR STRATIFICATION - Pospielov, S. V.; Opara, M. M.; Panchenko, K. S.; Zdor, V. M.; Solop, V. Ya. (Scientific Progress & Innovations, 2021)
The sowing qualities of seeds of medicinal plants: forest mallows (Malva sylvestris L.), coneflower (Echinacea purpurea (L.) Moench.), pale coneflower (Echinacea pallida (Nutt.) Nutt.), St. John's wort (Hypericum perforatum L.) cornflower (Centaurea cyanus L.) depending on the effect of stratification at a temperature of + 3 0C for 15, 30 and 45 days, were studied. The control was seeds, which were stored for the same period at a temperature of + 20 0C. In the seeds of forest mallows after stratification lasting 15 days, the germination energy increased significantly, by 65.6 %, and laboratory germination – by 46 % relative to the control; longer holding of the seeds was ineffective. In Echinacea purpurea the stratification significantly increased these indicators. Germination energy increased by 9–20 % and amounted to 78–82 %, and laboratory germination – by 10.2–13.4 % and reached 93 % after 45 days of stratification. As a result of stratification of pale coneflower seeds, germination energy after 15 days increased 1.3 times (up to 72 %), after 30 days – 1.36 times (up to 79 %), and after 1.5 months – 1.26 times (up to 82 %) relative to the control. Similar patterns were observed in determining laboratory germination. Our studies of cornflower seeds show that stratification for 15 days did not lead to a significant increase in both germination energy and laboratory germination. Longer duration of reduced temperatures led to a significant increase in germination energy by 7.5–10.0 %, and did not significantly affect laboratory germination (+3.4 % – + 5.7 % relative to the control). The study of the stratification effect on St. John's wort seeds shows that after 15–30 days of stratification, germination energy increased by 2–3 % in comparison with the control, and after 45 days – by 13 %. Laboratory germination increased by 1.05; 1.09; 1.18 times, respectively, which indicates the effectiveness of keeping the seeds of St. John's wort for 1.5 months at low temperatures. The conclusion about the efficacy of applying stratification of seeds of medicinal crops has been made.